Movement behavior of satellite-tagged leatherback turtles from Panama in response to chlorophyll, primary productivity, temperature, and eddy kinetic energy - Guzman, Hector M. (2024)
Leatherback turtles Dermochelys coriacea are globally endangered. This study tracked 30 individuals from the North Atlantic population tagged on the Caribbean Panama rookery (San San Pond Sak protected area, Bocas del Toro) over a period of 3 yr. We used satellite telemetry to investigate the probability that turtles switched between migration and foraging behavioral states as a function of environmental variables. We mapped the extensive migratory routes of these turtles and analyzed these using data derived from remote sensing, including chlorophyll, productivity, and sea surface temperature (SST), to assess how these influence their migratory and foraging behaviors. We also considered oceanographic processes, i.e. mesoscale eddies coinciding with the turtles’ migration paths, to understand their behavioral responses. Our observations revealed that while some turtles undertook extensive migrations to high-use areas in the Northeast and Northwest Atlantic, the majority remained within the boundaries of the Gulf of Mexico. The study effectively differentiated migration and feeding behavior, noting a clear positive relationship between feeding activities and chlorophyll concentration, while productivity played only a marginal role, and no influence was found for SST and mesoscale eddies. This study advances knowledge of North Atlantic leatherback turtle migrations, underscoring the importance of integrated, multidisciplinary marine conservation efforts. Understanding the impact of climate warming on migration paths and food source availability necessitates a holistic approach encompassing changes in physical oceanography, nutrient dynamics, and interactions from plankton to higher trophic levels. Additionally, as leatherback turtles traverse various international territories, the research emphasizes the need for collaborative data collection for their effective protection.